The Use of Yeşilçam Actors in Television Advertising: A Semiological Analysis and Comparison of Ziraat Bank Advertising Films - Tanyıldızı, Nural İmik; Acar, Hacı Mehmet (My University, 2020)
In today's world, advertising is possible everywhere. Advertisements that have appeared in variousforms since its existence have influenced the masses. Various products and services were promoted. Oneof the most widely used commercials is television commercials. Many commercial organizations try toreach the target audience by using television commercials. In this research, commercial films usingYeşilçam actors were examined. The sample of the research is the commercial films made by Ziraat Bankfor the 124th and 155th years. Different characters of Yeşilçam are used in these films. The aim of theresearch is to reveal the contribution of the use of Yeşilçam actors to the advertising messages. Theadvertising messages are intended to be explained with the relationship between the Yeşilçam actors.Semiotic analysis method was used in the analysis of advertising films. The role of the indicators relatedto Yeşilçam in the message transfer to the target audience was tried to be explained. Both films shot atdifferent periods were compared. Common and different aspects of commercial films were evaluated. Asa result of the research, it was found that the advertisements using Yeşilçam actors gave positive messages to the target audience. With these advertisements, both corporate promotion and economic motivation were tried to be provided in the society.
Keywords: İletişim; Film; Radyo; Televizyon; Sanat